Synthesis and redox catalysis of Carbodiphosphorane ligated stannylene - Zhuchunguang Liu; Zhijun Wang; Huan Mu; Yihan Zhou; Jiliang Zhou; Zhaowen Dong (Nature Communications)
Abstract Heavier group 14 carbene analogues, exhibiting transition-metal-like behavior, display remarkable capability for small molecule activation and coordination chemistry. However, their application in redox catalysis remains elusive. In this paper, we report the synthesis and isolation of a stannylene with carbodiphosphorane ligand. The nucleophilic reactivity at the divalent tin center is elucidated by computational and reactivity studies. Moreover, this stannylene exhibits catalytic activity in the hydrodefluorination reaction of fluoroarenes. Mechanistic investigations into the elementary steps confirm a SnII/SnIV redox cycle involving C–F oxidative addition, F/H ligand metathesis, and C–H reductive elimination. This low-valent SnII catalytic system resembles the classical transition metal catalysis. Notably, this represents metallomimetic redox catalysis utilizing carbene analogue with heavier group 14 element as a catalyst.